1992
DOI: 10.1002/art.1780350509
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biogenic amine metabolites in fibromyalgia/fibrositis syndrome and rheumatoid arthritis

Abstract: Objective. To compare the levels of biogenic mines in the cerebrospinal fluid (CSF) of primary fibromyalgia syndrome (PFS) patients with those in the CSF of controls.Methods. Metabolites of serotonin, norepinephrine, and dopamine were identified in CSF, using high performance liquid chromatography with coulometric detection.Results. CSF levels of metabolites from all 3 neurotransmitters were lower in PFS patients than in controls . Conclusion.A low rate of turnover of several neurotransmitters supports the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
230
1
24

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(260 citation statements)
references
References 31 publications
5
230
1
24
Order By: Relevance
“…For example, low levels of biogenic amines (22) and high levels of substance P (23) have been found in the cerebrospinal fluid in FM. Abnormalities in imipramine uptake receptors have also been noted (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, low levels of biogenic amines (22) and high levels of substance P (23) have been found in the cerebrospinal fluid in FM. Abnormalities in imipramine uptake receptors have also been noted (24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with fibromyalgia have reduced levels of biogenic amine metabolites, including dopamine, norepinephrine, and serotonin, in their cerebrospinal fluid [6,7]. It has been suggested that decreased iron stores lead to a reduced production of biogenic amines since iron is essential for neurotransmitter synthesis [8].…”
Section: Fibromyalgia Is a Disorder Characterized By Chronic Widesprementioning
confidence: 99%
“…Animal models suggest that depletion of monoaminergic neurotransmitters in the spinal cord, thalamus, and prefrontal cortex can cause chronic muscular pain, hyperalgesia, allodynia, and depression, which can be attenuated by treatment with serotonin and norepinephrine reuptake inhibitors (SNRIs) or pregabalin (11). Human studies confirm that patients with fibromyalgia have lowered levels of monoamines (12) in their cerebrospinal fluid and higher levels of substance P (13) and nerve growth factor (14). Serotonin and norepinephrine are thought to be the key neurotransmitters in the descending pain inhibitory system, and dopamine also appears to be involved in pain control in the central nervous system (15,16).…”
mentioning
confidence: 99%